2020
DOI: 10.1055/a-1287-2546
|View full text |Cite
|
Sign up to set email alerts
|

Gesundheitsökonomische Aspekte der Corona-Krise in der Schweiz: Resultate des COVID-19 Social Monitor

Abstract: ZusammenfassungNach Ausbruch der Corona-Pandemie wurde in der Schweiz Mitte März ein landesweiter Lockdown beschlossen. Dieser hatte extreme Auswirkungen auf das soziale Leben und die Gesundheitsversorgung. Der COVID-19 Social Monitor zeigt einige dieser gesellschaftlichen Veränderungen über die Zeit des Lockdowns und danach auf. Die Ergebnisse zeigen, dass in der akuten Phase des Lockdowns zwischen rund 50 % (Hausärzte) und über 90 % (Zahnärzte) der medizinischen Behandlungen nicht beansprucht wurden. Ausserd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Since there was no longer a formal treatment ban in Switzerland, these reductions can probably be attributed to a reaction of the hospitals to the pandemic situation (higher needs for intensive care units [ 4 ], staff shortages due to covid-infections) and to changes in patients’ demand for health services. Based on Swiss survey data, Höglinger et al [ 5 ] found that both during and after the lockdown, numerous patients voluntarily refrained from seeking "planned or necessary" medical treatments "because of Corona". Similarly, a reduction in costs and consultations during the spring lockdown was observed in the Swiss outpatient sector [ 25 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since there was no longer a formal treatment ban in Switzerland, these reductions can probably be attributed to a reaction of the hospitals to the pandemic situation (higher needs for intensive care units [ 4 ], staff shortages due to covid-infections) and to changes in patients’ demand for health services. Based on Swiss survey data, Höglinger et al [ 5 ] found that both during and after the lockdown, numerous patients voluntarily refrained from seeking "planned or necessary" medical treatments "because of Corona". Similarly, a reduction in costs and consultations during the spring lockdown was observed in the Swiss outpatient sector [ 25 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since there was no longer a formal treatment ban in Switzerland, these reductions can probably be attributed to a reaction of the hospitals to the pandemic situation (higher needs for intensive care units (4), staff shortages due to covid-infections) and to changes in patients' demand for health services. Based on Swiss survey data, Höglinger et al (5) found that both during and after the lockdown, numerous patients voluntarily refrained from seeking "planned or necessary" medical treatments "because of Corona". Similarly, a reduction in costs and consultations during the spring lockdown was observed in the Swiss outpatient sector (25,49).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these restrictions on the supply side, patients' demand for medical services may have declined due to fears of a Covid-19 infection or to self-imposed restraints to avoid additional burden on the strained healthcare system. Evidence for these demand-side effects from patients for the period of the spring lockdown and subsequent months can be found in a representative Swiss survey study (5).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, more diverse participants should have been involved in the evaluation of the guide. The project was conducted during the COVID-19 pandemic, when doctor's visits were reduced to the minimum [35,36], and patients were probably less willing to participate. Additionally, the discussed skepticism in respect to patient-provider communication with the guide has led to a difficult recruiting process and a smaller, less diverse sample than planned.…”
Section: Discussionmentioning
confidence: 99%